2014
DOI: 10.1038/pcan.2014.23
|View full text |Cite
|
Sign up to set email alerts
|

The association between insurance status and prostate cancer outcomes: implications for the Affordable Care Act

Abstract: Insured men with prostate cancer are less likely to present with metastatic disease, more likely to be treated if they develop high-risk disease and are more likely to survive their cancer, suggesting that expanding health coverage under the ACA may significantly improve outcomes for men with prostate cancer who are not yet eligible for Medicare.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 36 publications
1
47
1
Order By: Relevance
“…Although previous studies have indicated that insurance status is associated with a reduction in racial treatment disparities among men diagnosed with localized CaP, we found that racial disparities were only mitigated among men with Medicaid coverage. This appears to be due to factors that we can only hypothesize: perhaps more equal screening, detection of disease, adjuvant care, or posttreatment support is driving the reduced disparate outcomes.…”
Section: Discussioncontrasting
confidence: 97%
“…Although previous studies have indicated that insurance status is associated with a reduction in racial treatment disparities among men diagnosed with localized CaP, we found that racial disparities were only mitigated among men with Medicaid coverage. This appears to be due to factors that we can only hypothesize: perhaps more equal screening, detection of disease, adjuvant care, or posttreatment support is driving the reduced disparate outcomes.…”
Section: Discussioncontrasting
confidence: 97%
“…U.S. Census data published in 2012 showed that 15.4%, or 48 million Americans, went uncovered by health insurance, and Medicaid covered 16.4%, or 51 million Americans (DeNavas-Walt, US census bureau, 2013). Lack of insurance coverage has been associated with worse survival and postoperative complications in critical illness (21), trauma (22), breast cancer (23), uterine cancer (24), colorectal cancer (25, 26), prostate cancer (27), diffuse large cell lymphoma (28), head and neck cancer (29), and lung cancer (30). Attributable causes for worse clinical outcomes in uninsured Americans include more advanced disease at time of diagnosis, fewer diagnostic tests performed, and decreased healthcare literacy (31, 32).…”
Section: Discussionmentioning
confidence: 99%
“…1 Reducing sociodemographic disparities in high-risk cancers has been a major goal of the American Cancer Society and other major cancer organizations for the last 2 decades. [5][6][7][8][9] Disparities in cancer care certainly present a barrier to mitigating disparities in cancer outcome, although it is unclear whether reducing disparities in care patterns would actually translate to better cancer outcomes. [5][6][7][8][9] Disparities in cancer care certainly present a barrier to mitigating disparities in cancer outcome, although it is unclear whether reducing disparities in care patterns would actually translate to better cancer outcomes.…”
Section: Introductionmentioning
confidence: 99%